Developmentand validation ofalgorithms for etimating chlorophyll-a concentration using sentinel-2 satellite and field radiometry in Brazilian semiarid reservoirs - Aranha, Thaís Regina Benevides Trigueiro (2022)
Providing continuous monitoring of the water resource quality in semi-arid tropical areas is of great societal importance. To contribute to this monitoring, this study made use of highresolution remote sensing data in Ceará and Rio Grande do Norte reservoirs through Sentinel- 2 Level-1 and Level-2 satellite images, during the period of November/2015 to December/2019, and field radiometry, from November/2008 and December/2015, to estimate the concentration of chlorophyll-a (chl-a), the main indicator of the trophic state of aquatic environments. To this end, Empirical and semi-analytical bio-optic models available in the literature were tested, as well as a new model for the retrieval of chl-a in the study region was proposed. All models analyzed cover the spectral region of red and near infrared (NIR), and chl-a concentration data collected in-situ were used to calibrate and validate the models. After statistical tests, the model proposed in this study and an empirical model of three bands widely used in interior water literature performed satisfactorily, with R² = 0.87 and R² = 0.80, respectively, for calibration data. Data on wind direction and speed, solar radiation and reservoir volume were used to generate a conceptual model to analyze the behavior of chl-a in the surface waters of the Castanhão reservoir. During 2019, the reservoir water quality showed strong variation, with concentration fluctuating from 30 to 95 μg/L We showed that the end of the dry season is marked by strong eutrophic conditions corresponding to very low water inflows into the reservoir. During the rainy season there is a large decrease in the chl-a concentration following the increase of the lake water storage. During the following dry season, satellite data show a progressive improvement of the trophic state controlled by wind intensity that promotes a better mixing of the reservoir waters and inhibiting the development of most phytoplankton.